2002
DOI: 10.1074/jbc.m200272200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rat NDRG2 (N-Myc Downstream Regulated Gene 2), a Novel Early Mineralocorticoid-specific Induced Gene

Abstract: The early phase of the stimulatory action of aldosterone on sodium reabsorption in tight epithelia involves hormone-regulated genes that remain to be identified. Using a subtractive hybridization technique on isolated renal cortical collecting ducts from rats injected with a physiological dose of aldosterone, we have identified an early response cDNA highly homologous to human and murine NDRG2 (N-Myc downstream regulated gene 2), which consists of four isoforms and belongs to a new family of differentiation-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 41 publications
(43 reference statements)
4
101
1
1
Order By: Relevance
“…N-myc downstream regulated gene 2 (NDRG2), a member of a new family of differentiation-related genes, is highly expressed in adult brain, salivary gland, and skeletal muscle (Boulkroun et al, 2002;Qu et al, 2002). This family is comprised of four members, NDRG1-4, and the expression pattern of these genes is differs during development (Qu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…N-myc downstream regulated gene 2 (NDRG2), a member of a new family of differentiation-related genes, is highly expressed in adult brain, salivary gland, and skeletal muscle (Boulkroun et al, 2002;Qu et al, 2002). This family is comprised of four members, NDRG1-4, and the expression pattern of these genes is differs during development (Qu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Given the roles of NDRG2 in renal function [4,5] and since both FXR and NDRG2 are enriched in kidney, we investigated whether Ndrg2 expression was regulated by FXR activation in this organ. The i.p.…”
Section: Ndrg2 Expression Is Induced By Activated Fxr In Kidneymentioning
confidence: 99%
“…Notably, in addition to tumor suppression, NDRG2 has also been related to the regulation of sodium gradient in several reports. First, NDRG2 was identified as a mineralocorticoid-induced gene in renal cortical collecting duct, the site of aldosterone-regulated sodium absorption [4]. Later, studies in heterologous expression systems showed that co-expression of NDRG2 and ENaC resulted in a stimulation of ENaC-mediated Na + currents [5].…”
Section: Treatment Of Transfected Cells With Natural (Cdca) or Synthementioning
confidence: 99%
See 2 more Smart Citations